Analisis Yuridis Pertanggungjawaban Notaris terhadap Pemalsuan Tanda Tangan oleh Penghadap dalam Akta Autentik - Adi Utama Pandapotan Lubis (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
A Notary plays an important part in creating legal certainly and legal protection for the people. The criminal act which usually occurs is related to Article 263, Article 264 and Article 266 of HUHP (The Criminal Code). Concerning a Notary’s criminal act in deed forgery or false testimony done by any party, UUJN (Notarial Act) does not specifically regulate any crimenal case because, based on the principle of legality as it is the principles in the KUHP. A Notary as a public official should do his noble task in helping people solve their legal problems. Therefore, he should be cautious, prudent, and increase his knowledge of any applicable legal provisions well so that the deeds he has made will not cause people to get involved in dispute.